A mixed methods systematic review of studies examining the relationship between housing and health for people from refugee and asylum seeking backgrounds. (September 2018) - Ziersch, Anna; Due, Clemence
Abstract: Housing is an important social determinant of health and a key element of refugee integration into countries of resettlement. However, the way in which housing may affect mental and physical health for refugees and asylum seekers has not been systematically examined. This systematic review aimed to explore the effects of housing on health and wellbeing for this population, in order to identify key pathways for public health interventions. The review was undertaken following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Social Care Institute for Excellence (SCIE) guidelines. We identified publications through a search of Medline, PsychInfo, Scopus, Web of Science, Embase, CINAHL, Cohrane Library, Google, ProQuest, OpenGrey, MedNar and WHOLIS. Eligibility criteria included: publication in English between 1997 and 2017, with findings pertaining to the relationship between housing and health for refugees and/or asylum seekers. Out of 2371 items, 25 papers were included with a further five identified through reference lists. Eleven of the papers explored housing and health for those refugees and asylum seekers living within refugee camps, with 19 focusing on countries of resettlement. All studies identified housing issues for refugees and asylum seekers, with physical housing conditions particularly poor in refugee camps, and issues of affordability, suitability, insecure tenure and mobility as well as difficulties securing housing also highlighted in countries of resettlement. Consistent relationships were found between physical aspects of housing and physical and mental health, with other aspects of housing such as safety and overcrowding linked to mental health. There were a number of methodological issues with most of the studies, making it difficult to specify precise pathways. However, improvements to housing quality particularly in refugee camps, and targeted housing interventions more generally for refugees and asylum seekers would likely have an important public health benefit. Highlights: Synthesis of studies on housing and health link for refugees and asylum seekers. Limited research in either refugee camps or resettlement countries. Evidence of the health impacts of housing problems, particularly in refugee camps. Methodological limitations identified in the evidence base. A range of potential public health interventions, but requires specific evaluation.